Food Security in the Local Government: A SDGs Perspective of Evaluation of Dry Land Policy and Rice Production - Tening, Graciella Fortunata; Akbar, Paisal; Budiman; Burhan, Reksa; Rafdi, Hashfi; Low, Kah Choon (Universitas Muhammadiyah Malang, 2025)
Food security in Indonesia’s Underdeveloped, Frontier, and Outermost Regions (3T) is shaped not only by ecological and technical constraints but also by governance capacity. This study examines upland rice production trends in Mahakam Ulu Regency (2018–2023) and evaluates Regent Regulation No. 12 of 2021, which provides incentives to dryland farmers. Using qualitative document analysis of secondary data from statistical reports, government documents, and credible media, the study finds that production has declined due to limited infrastructure, restricted access to inputs, and dependence on external supplies. Incentives have encouraged participation and capacity building but remain constrained by weak institutions and insufficient extension services. The findings highlight a design capacity mismatch in local policy implementation. This study contributes to governance and policy literature by showing how local food initiatives in peripheral regions intersect with the Sustainable Development Goals (SDGs), particularly SDG 2, SDG 1, SDG 4, SDG 8, and SDG 16. Strengthening institutions and embedding monitoring systems are recommended for sustainable outcomes.